2014
DOI: 10.4049/jimmunol.1401558
|View full text |Cite
|
Sign up to set email alerts
|

mTORC1-Dependent Metabolic Reprogramming Is a Prerequisite for NK Cell Effector Function

Abstract: The mammalian target of rapamcyin complex 1 (mTORC1) is a key regulator of cellular metabolism and also has fundamental roles in controlling immune responses. Emerging evidence suggests that these two functions of mTORC1 are integrally linked. However, little is known regarding mTORC1 function in controlling the metabolism and function of natural killer (NK) cells, lymphocytes that play key roles in anti-viral and anti-tumour immunity. This study investigated the hypothesis that mTORC1-controlled metabolism un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
474
5
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 384 publications
(530 citation statements)
references
References 42 publications
30
474
5
2
Order By: Relevance
“…NK cells rely on metabolic reprogramming for effector function. Inhibition of either glycolysis or the glycolytic regulator mammalian target of rapamycin complex 1 (mTORC1) results in diminished effector responses by NK cells, such as cytokine production (21,22). Therefore, we investigated the effect of obesity on pediatric NK cell metabolic reprogramming.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…NK cells rely on metabolic reprogramming for effector function. Inhibition of either glycolysis or the glycolytic regulator mammalian target of rapamycin complex 1 (mTORC1) results in diminished effector responses by NK cells, such as cytokine production (21,22). Therefore, we investigated the effect of obesity on pediatric NK cell metabolic reprogramming.…”
Section: Resultsmentioning
confidence: 99%
“…NK cells isolated from obese children killed significantly fewer K562 tumor cells compared with their lean counterparts ( Figure 2H). We also investigated lytic molecule expression by NK cells after coculture with K562 and showed that NK cells from obese children express reduced levels of both granzyme B and perforin when compared with lean controls ( Recent studies have shown that NK cell effector function is intrinsically linked to cell metabolism (21,22). NK cells rely on metabolic reprogramming for effector function.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The depletion of other nutrients may also indirectly impact glycolytic rates in immune cells by disrupting the activity of the metabolic regulator mTORC1 (22,23). Tryptophan and arginine can be depleted in the tumor microenvironment by the action of the enzymes indoleamine-pyrrole 2,3-dioxygenase (IDO) and arginase-1, respectively.…”
Section: Oxphos Facilitates Cellular Longevitymentioning
confidence: 99%
“…Preventing glycolytic metabolism in tumor-infiltrating effector lymphocytes by limiting glucose availability is one immune evasion strategy used by tumors (19)(20)(21). Disrupting glycolysis in effector T cells and NK cells inhibits the production of the proinflammatory cytokine IFN-γ and the expression of molecules important for cellular cytotoxicity (9,16,(22)(23)(24). Low glucose levels also enforce oxidative metabolism on tumor-infiltrating macrophages, which inhibits proinflammatory functions and promotes an antiinflammatory macrophage phenotype (25,26).…”
Section: Oxphos Facilitates Cellular Longevitymentioning
confidence: 99%